Generation of Optimal Switching Angle for Nine Level Cascaded H Bridge MLI Using Most Valuable Player Algorithm - G Devadasu, Kumar C, Vijaya Anand N, Hema Latha J, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Distributed generation (DG) sources often interfaced with grid by a Cascaded H-bridge multilevel inverter with a remote D.C source. The interface inverter has to adapt voltage on the either side of the grid and DG source while it has a control of active and reactive power exchange. The inverter terminal voltage is maintained based on frequency switching technique. However, in applications like micro grids are based on quality of output voltage at the point of common coupling. The present paper discusses an optimal frequency switching methodology that generates optimal fringing angle based on an evolutionary computing technique while maintaining the voltage level at PCC with a reduced harmonic distortion. Efficacy of the proposed method is illustrated by simulating a 9-level cascaded H bridge in MATLAB environment.